Application of the Principles of Legality and Due Process of Law in the Indonesian National Police Personnel Dispute: A Legal Analysis of the Jakarta Administrative Court Decision Number 50/G/2020/PTUN.JKT - Cordelia, Anastasia; Matulandi, Sabina Abigail; Lawira, William; Nugraha, Dwi Putra (Journal of Law, Politic and Humanities, 2026)
Penelitian ini bertujuan untuk menganalisis apakahpenerbitan keputusan tersebut telah memenuhi asas legalitasdalam hukum administrasi negara serta apakah proses pemeriksaan dan penerbitannya telah mencerminkan prinsipdue process of law dan memberikan perlindungan hukum yang adil bagi pihak yang bersangkutan. Metode yang digunakanadalah penelitian hukum normatif dengan pendekatanperaturan perundang-undangan, pendekatan kasus, dan pendekatan konseptual melalui analisis putusan pengadilan, peraturan perundang-undangan, dan literatur hukumadministrasi negara. Hasil penelitian menunjukkan bahwasecara kewenangan formal keputusan tersebut telah memilikidasar hukum yang sah, namun terdapat indikasi kelemahanpada aspek prosedural dan substansial yang berpengaruhterhadap penerapan asas legalitas secara utuh. Selain itu, proses pemeriksaan dinilai belum sepenuhnya mencerminkanprinsip due process of law karena terdapat kekurangan dalampemenuhan hak untuk didengar, transparansi, sertaobjektivitas pemeriksaan. Kesimpulan penelitian inimenegaskan bahwa penerapan asas legalitas dan due process of law dalam perkara PTDH tersebut belum sepenuhnyaterpenuhi secara optimal dalam praktik administrasikepolisian. The study aims to analyze whether the issuance of the decision complies with the principle of legality in administrative law and whether the examination and decision-making process reflects due process of law and provides fair legal protection for the concerned individual. This research uses a normative legal method with statutory, case, and conceptual approaches by analyzing court decisions, relevant legislation, and legal literature in administrative law. The findings indicate that while the decision has a valid formal legal basis in terms of authority, there are indications of deficiencies in procedural and substantive aspects affecting the full application of the principle of legality. In addition, the examination process does not fully reflect due process of law due to shortcomings in the right to be heard, transparency, and objectivity of the proceedings. The study concludes that the implementation of both the principle of legality and due process of law in this dismissal case has not been optimally fulfilled in police administrative practice.